2012
DOI: 10.3821/145.6.cpj268
|View full text |Cite
|
Sign up to set email alerts
|

The MyHealthCheckup Study: Training Graduate Students to Implement Cardiovascular Risk Screening Programs in Community Pharmacies

Abstract: Results:Among the 238 patients who participated (57% female, mean age 60.6 years), 67% had a body mass index (BMI) greater than 25 kg/m 2 , 52% had abdominal obesity, 58% reported insufficient physical activity and 14% were smokers. A total of 120 patients (51%) were taking antihypertensive medication, yet 63 (53%) had blood pressure readings above currently accepted targets. Higher BMI and physical inactivity were associated with increased rates of poorly controlled hypertension. ABSTRACT Conclusion:The scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Several prior studies have demonstrated that the use of health information technology and/or community health workers can promote improved hypertension control . Yet many of these programs required significant resources, and their durability, scalability, and generalizability to other settings was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have demonstrated that the use of health information technology and/or community health workers can promote improved hypertension control . Yet many of these programs required significant resources, and their durability, scalability, and generalizability to other settings was unclear.…”
Section: Discussionmentioning
confidence: 99%